Peran Mahasiswa Sebagai Implementator Program Kampus Mengajar dalam Gerakan Literasi Siswa (Studi Kasus di SDN Atas Awan Pusung Malang Puspo Pasuruan) - Dwi, Andhini; Sunandar, Asep; Supriyanto, Achmad (Universitas Negeri Malang, 2025)
The purpose of this study is to describe: (1) the preparations made by the campus teaching students in driving student literacy at SDN 1 Pusungmalang Puspo; (2) analysis of the challenges and obstacles of the campus teaching students in acting as implementers of the implementation of the program to improve student literacy at SDN 1 Pusungmalang Puspo; (3) strategies used by the campus teaching students in acting as implementers of the implementation of the program to improve student literacy at SDN 1 Pusungmalang Puspo; (4) the impact of the campus teaching program in improving student literacy at SDN 1 Pusungmalang Puspo. The research approach used is a qualitative method with a case study, the location was implemented at SDN Pusungmalang 1 Puspo Pasuruan, data collection techniques include observation interviews, and field data analysis and documentary studies. The data analysis process includes data collection, data condensation and drawing conclusions using Nvivo 12 pro software. The validity of the research data uses triangulation techniques. This study reveals various findings related to the implementation of the Campus Teaching Program in improving student literacy at SDN Pusungmalang 1 Puspo. Students start with thorough preparation, following training provided by the program, which includes understanding student needs, adjusting learning materials, and using relevant media to support the learning process. However, they face several challenges, such as limited facilities at school, including limited access to books and technology, as well as difficult-to-reach geographical conditions and low student interest in reading.